Delayed diagnosis in children with autism spectrum disorder or intellectual disability - Janaína Aparecida de Oliveira Augusto; Carolina Kulcsar Caravieri; Rodrigo Genaro Arduini; Décio Brunoni; Sylvia Maria Ciasca; Maria Cristina Triguero Veloz Teixeira (Dementia & Neuropsychologia)
ABSTRACT In the developing countries, there is a long delay between parents’ first concerns and the diagnosis of neurodevelopmental disorders such as autism spectrum disorder (ASD) and intellectual disability (ID). Objective: To verify the time interval between the first concerns reported by parents and the diagnosis of ASD and ID in a pediatric neurology outpatient clinic in the public health network in Brazil, and to verify any association between indicators of cognitive functioning and behavioral and emotional problems. Methods: One hundred and six children diagnosed with ID (n=69) and ASD (n=37), with a mean age of 10.03 years; standard deviation (SD)=2.2. The inclusion criteria were diagnoses of ID and ASD, and the exclusion criteria were comorbid conditions such as attention-deficit/hyperactivity disorder and specific learning disorder. Results: The mean age of reported first symptoms was 29.9 months (SD=19.5) for ASD and 37.9 months (SD=19.5) for ID; and the mean time from first concerns to diagnosis of ID was 6.8 years (SD=2.2) and 6.6 years (SD=2.7) for ASD. Children with ID scored significantly lower than those with ASD cognitive functioning (t [97]=-16.22, p<0.001). Children with ID had higher mean scores for externalizing problems (M=62.20; SD=11) and those with ASD had higher mean scores for internalizing problems (M=66.71; SD=10.01). Conclusion: The results indicated a late diagnosis in the sample and, given the mental health care received, the data highlight the need for training primary care professionals to identify and diagnose ASD and ID at an early stage.